Review of De Young,"Life & Death of a Rural American High School: Farewell Little Kanawha" - Howley, Craig; Theobald, Paul (Education Policy Analysis Archives, 1995)
lan DeYoung's story of the circumstances surrounding the birth, growth, and death of a high school in rural West Virginia is an intellectual contribution of the first order. And Farewell Little Kanawha is certainly one of the best stories to be told by an educational researcher in recent decades. Its strength derives in large measure from DeYoung's deftness in crossing disciplinary borders. The interplay of economics, sociology, history (both oral and documentary), anthropology, and biography render this story far more compelling than most educational research. DeYoung bases his narrative, in fact, on C. Wright Mills' precept that social science worth doing must interpret the intersection of biography and history. Mills was the wisest and best American sociologist and DeYoung is among a very small contingent of scholars concerned with rural education to embrace his advice.